Pengembangan Media Pembelajaran Sesorah Dengan Video Pepipak (Pembelajaran Pidato Ngapak) untuk Siswa Kelas IX SMP di Tegal - fadhliani, nur izza; Indiatmoko, Bambang; Yuwono, Agus (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Objectives of the research are (1) to know the necessity of learning Javanese speech, (2) to know the prototype development of media pepipak video, (3) to know the product validation of media pepipak video for speech learning. This research uses the research and development approach. The development of this media is through five steps, i.e (1) potential problems, (2) data collection, (3) product design, (4) test expert validation, (5) design improvement. The instrument of this research is the nontest instrument in the form questionnaire. Based on the analysis results, the necessity of learning Javanese speech shows the teacher and the students need media pepipak video. The prototype results of media pepipak video have duration 04.18 minutes which consist of: (1) opening of media, (2) content of media, (3) closing of media. The test expert validation of the materials and media are obtained percentage 71.76% and 78,82% which includes a good category with some revisions, that is on the opening of media which is added the identity of the media maker.